2003
DOI: 10.1530/eje.0.1480635
|View full text |Cite
|
Sign up to set email alerts
|

Acute hyperglycemia and activation of the beta-adrenergic system exhibit synergistic inhibitory actions on growth hormone (GH) releasing hormone-induced GH release

Abstract: Objective: Acute hyperglycemia stimulates somatostatin (SRIH) release by the hypothalamus which, in turn, suppresses growth hormone (GH) secretion from the anterior pituitary gland. Although it has been suggested that the cholinergic pathway mediates glucose-induced SRIH release, other regulatory systems have not been examined. Therefore, we investigated whether blocking or activating the b-adrenergic pathway alters glucose-mediated inhibition of GH release. Design and methods: One set of experiments was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…However, there was no further suppressive effect on TSH secretion by the combined stimulation of glucose and isoproterenol. These results are in contrast to the effects of glucose and isoproterenol on GHRH-induced GH secretion where the degree of suppression induced by combined glucose and isoproterenol treatment was significantly higher than that achieved by glucose and isoproterenol alone [10]. This discrepancy could be attributed to the differences in responsiveness of GH and TSH to hypothalamic SRIH.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…However, there was no further suppressive effect on TSH secretion by the combined stimulation of glucose and isoproterenol. These results are in contrast to the effects of glucose and isoproterenol on GHRH-induced GH secretion where the degree of suppression induced by combined glucose and isoproterenol treatment was significantly higher than that achieved by glucose and isoproterenol alone [10]. This discrepancy could be attributed to the differences in responsiveness of GH and TSH to hypothalamic SRIH.…”
Section: Discussioncontrasting
confidence: 82%
“…Our laboratory, as well as others, has observed that both of these stimuli block GHRH-induced GH release [10][11][12][13]. Recently we have reported that the degree of suppression of the GH response to GHRH, initiated by glucose and the badrenergic agonist, isoproterenol, was comparable, while the combined effects were significantly higher than that achieved by glucose and isoproterenol alone [10]. In addition, propranolol, a b-adrenergic antagonist was not able to block glucose-induced suppression of GHRH-stimulated GH release.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, since P is known to: i) traverse the blood-brain barrier [35] and ii) affect the release of several hypothalamic releasing/inhibiting hormones and consequently the secretion of several pituitary hormones which may directly and/or indirectly, via hormones from their target glands in the periphery, [49][50][51] modulate T-cell differentiation/maturation [52], centrally-regulated mechanisms may mediate some of the observed effects of P in thymi.…”
Section: Discussionmentioning
confidence: 99%
“…All of these tests should inevitably accompany a change of SST secondary to either the change in glucose levels or the action of somatostatin analogues. Rapid inhibitory effect of hyperglycemia upon GH secretion may be due to somatostatin from hypothalamus (5), and it has been also suggested that this somatostatin release accompanies the modulation of SST (6). Therefore, the change in SST can be regarded as an intermediate link between glucose and GH secretion, and integrated analysis of the results of these tests could be a practical tool to evaluate SST in pituitary adenomas.…”
Section: Introductionmentioning
confidence: 99%